Christian ethics and migration in Germany since 2015: a critical response to Robert Heimburger. Issue 5 (September 2019) - Feiler, Therese
Grounded in experiences in German migration policy since 2015, this article criticizes Robert Heimburger's approach to migration due to its lack of theological distinctions.